India's Comparative Advantage and Trade Specialization in the Wheat Sector vis-à-vis the BIMSTEC Countries - Md. Monzur Hossain; Partha Acharjee; Mithun Bairagi (مجلة ديالى للعلوم الزراعية)
Currently, the global community is observing the increasing significance of Asian countries in international trade, and 48 Asian nations, India's wheat sector, has experienced a significant reorganization in generating revenue and employment prospects. The research aimed to analyze the comparative advantage and trade specialization in the wheat sector enjoyed by India compared to other member countries of BIMSTEC using the OEC database from 2013 to 2022. The Balassa and Lafay index highlights India's relative competitiveness and extent of trade specialization. To compare the pair-wise comparison between the member countries, Games-Howell Post-Hoc estimation was employed since the normality and homogeneity of data hardly provide any scope to apply one-way ANOVA. Finally, the study concluded that India enjoyed a high degree of competitiveness in the wheat market as compared to other BIMSTEC members during the study period. Consequently, the results indicate that India is enjoying a robust advantage in the global wheat trade market, in general, and in the BIMSTEC region, in particular. Based on the result, this study prescribed that since BIMSTEC will implement trade facilitation in 2030, the identification of specific products like wheat may be incorporated into the list for greater regional trade integration.